「免疫抑制的なシグナル伝達機構」が免疫反応を賦活するとき：カンナビノイドCB2受容体の場合 - 野崎, 千尋; Andreas, Zimmer; 細木, 春花 (日本薬理学会年会要旨集, 2023)
It is widely known that cannabinoid type 2 (CB2) receptor deficiency enhances inflammatory response and further symptoms in various animal models of inflammation, allergy, or cancer. As CB2 receptors are inhibitory Gi/Go G-protein coupled receptors and as major expression site of CB2 receptors are immune cells, it is no wonder that lack of CB2 receptor might lead the exacerbated inflammation. We therefore hypothesized that lack of CB2 receptor might also enhance the high fat diet (HFD)-induced peripheral neuroinflammation. However, surprisingly, CB2 receptor knockout animals (CB2-KOs) showed the significant resistance to the HFD-induced neuroinflammation. Namely, 5-week feeding of HFD induced substantial hypersensitivity in WT mice, while tactile sensitivity of HFD-fed CB2-KO remained intact. In the same animals, we further found the robust upregulation of infiltrated macrophages, chemokine receptor CXCR4 expression and modified differentiation of splenic myeloid-derived suppressor cells (MDSCs) in HFD-fed WT animals, but not in either HFD-fed CB2 knockout mice or standard fat diet (SFD)-fed WT and CB2-KO controls. Based on these results, we will propose that CB2 receptors might have the bipolar regulatory role to chemokine receptor-mediated inflammatory response through the modulation of splenic MDSC differentiation, which in the end enhance or inhibit the development of neuroinflammation depending on its cause.